Fostering the Mediating Role of the Feeling of Belonging to an Organization Among Romanian Members of Generation Z - Botezat, Elena; Fotea, Silvia L.; Marici , Marius; Fotea, Ioan S. (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
The addition of Generation Z/Centennials to the workplace landscape will bring about new challenges for the management of any organization. To tackle the changing work environment and workforce, we conducted a survey-based empirical exploratory study among students in economics from two universities located in the western part of Romania. Our study proposes an alternative view of the motivational potential, including the feeling of belonging to an organization in work settings. The aim was to explore the potential for the feeling of belonging to play the role of mediator between four distinct career attitudes and the turnover intention in the specific case of Romanian Generation Z members. Additionally, we investigated which variables are significant predictors for the feeling of belonging to an organization. The results indicate that is efficient to invest in creating belongingness for those Generation Z members inclined towards making moves between jobs and organizations (OMPA), for those who present the mental capacity to be mobile (BMA) and for those who can be adaptive in terms of performance and learning demands (SDA). For those Romanian Generation Z members who use their internal values to provide guidance and measure for success, including the feeling of belonging to an organization in work settings seems to be inefficient.